ANNA FITZGERALD’S REBELLION TOWARDS HER MOTHER IN HER EARLY ADOLESCENCE PERIOD AS DEPICTED IN NICK CASSAVETES’ MY SISTER’S KEEPER - AGHTSA, ZEAL FACHRUDDIN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Rebellion, Anna Fitzgerald, My Sister Keeper. My Sister Keeper is the one of the films directed by Nick Cassavetes explored the problem of family. Anna as a major character in the film is in the difficult position, when she is eleven,  she begins to think about herself. She wants to stop donates her body’s part to her sister, Kate, who is suffering from Leukimia. Sara and Brian tried to make programmed baby, that was Anna, because Kate needs a perfect match donor for her life. The strong desires of Anna’s mother to care Kate’s sickness using Anna’s part of body make Anna powerless. This problem arises more complicated when Anna sues her parents to court for her medical emancipation. In line with that, the problems of the study proposed by the researcher is; how is Anna’s rebellion toward her mother in her early adolescence period in Nick Cassavete’s My Sister’s Keeper?.This research is aimed to describe how is Anna’s rebellion towards her mother inMy Sister Keeper film. This study uses Carl Pickhard’s theory of rebellion in earlyadolescence to conduct the research. Moreover, the data of this research are collected from My Sister Keeper and then analyzed in terms of how Anna Fitzgerald’s rebellion to her mother.The researcher found Anna’s rebellions towards her mother which arecategorized by emotional changes and cognitive changes. In the emotional changes there are concern on body image, high expectation and unpredictable changes of mood. In the cognitive changes, there are complex thought and ability to express feelings.The researcher hopes the future researcher who is interested in My Sister Keeperas the object can use Sigmund’s Freud theory and give new complete references.